Inflamm-Aging-Related Cytokines of IL-17 and IFN-γ Accelerate Osteoclastogenesis and Periodontal Destruction - Jingyi Tan; Anna Dai; Lai Pan; Lan Zhang; Zhongxiu Wang; Ting Ke; Weilian Sun; Yanmin Wu; Pei-Hui Ding; Lili Chen (Journal of Immunology Research)
Periodontal disease (PD), as an age-related disease, prevalent in middle-aged and elderly population, is characterized as inflammatory periodontal tissue loss, including gingival inflammation and alveolar bone resorption. However, the definite mechanism of aging-related inflammation in PD pathology needs further investigation. Our study is aimed at exploring the effect of inflamm-aging-related cytokines of interleukin-17 (IL-17) and interferon-γ (IFN-γ) on osteoclastogenesis in vitro and periodontal destruction in vivo. For receptor activator of nuclear factor-κB ligand- (RANKL-) primed bone marrow macrophages (BMMs), IL-17 and IFN-γ enhanced osteoclastogenesis, with the expression of osteoclastogenic mRNA (TRAP, c-Fos, MMP-9, Ctsk, and NFATc1) and protein (c-Fos and MMP-9) upregulated. Ligament-induced rat models were established to investigate the role of IL-17 and IFN-γ on experimental periodontitis. Both IL-17 and IFN-γ could enhance the local inflammation in gingival tissues. Although there might be an antagonistic interaction between IL-17 and IFN-γ, IL-17 and IFN-γ could facilitate alveolar bone loss and osteoclast differentiation.